Traumatic Brain Injury as Frequent Cause of Hypopituitarism and Growth Hormone Deficiency: Epidemiology, Diagnosis, and Treatment - Gasco, Valentina; Cambria, Valeria; Bioletto, Fabio; Ghigo, Ezio; Grottoli, Silvia (Frontiers in Endocrinology, 2021)
Traumatic brain injury (TBI)-related hypopituitarism has been recognized as a clinical entity for more than a century, with the first case being reported in 1918. However, during the 20th century hypopituitarism was considered only a rare sequela of TBI. Since 2000 several studies strongly suggest that TBI-mediated pituitary hormones deficiency may be more frequent than previously thought. Growth hormone deficiency (GHD) is the most common abnormality, followed by hypogonadism, hypothyroidism, hypocortisolism, and diabetes insipidus. The pathophysiological mechanisms underlying pituitary damage in TBI patients include a primary injury that may lead to the direct trauma of the hypothalamus or pituitary gland; on the other hand, secondary injuries are mainly related to an interplay of a complex and ongoing cascade of specific molecular/biochemical events. The available data describe the importance of GHD after TBI and its influence in promoting neurocognitive and behavioral deficits. The poor outcomes that are seen with long standing GHD in post TBI patients could be improved by GH treatment, but to date literature data on the possible beneficial effects of GH replacement therapy in post-TBI GHD patients are currently scarce and fragmented. More studies are needed to further characterize this clinical syndrome with the purpose of establishing appropriate standards of care. The purpose of this review is to summarize the current state of knowledge about post-traumatic GH deficiency